Endothelial immunocytochemical expression of pituitary IL-1β and its relation to ACTH-positive cells is regulated by corticosterone in the male rat. (November 2017) - Iglesias-Osma, María Carmen; Blanco, Enrique J.; Carretero-Hernández, Marta; García-Barrado, María José; Catalano-Iniesta, Leonardo; Carretero, Manuel; Sánchez-Robledo, Virginia; Carretero, José
Highlights: We analyzed the relationship among the pituitary cells expressing IL-1β and ACTH. Immunocytochemical expression of both polypeptides was studied in stress situations. IL-1β was located in pituitary endothelial cells at the hypophyseal portal vessels. Pituitary endothelial expression of IL-1β was independent of the treatment. Endothelial pituitary IL-1β could regulate ACTH in a paracrine fashion. Abstract: Interleukin-1 beta (IL-1β) is a cytokine linking the neuroendocrine system and metabolic homeostasis. We have previously demonstrated the relevance of IL-1β for maintaining the pituitary ACTH-producing cells by immuno-blocking its effects in pituitary cultures. However, the morphological characteristics and the intimate relationship of the pituitary cells expressing IL-1β and ACTH remain unknown. For determining pituitary variations of immunoreactivity for IL-1β and its relation with ACTH-positive cells under stress situations, we performed an immunohistochemical analysis of the expression of IL-1β and ACTH in the pituitary gland of adult rats, in the absence or presence of corticosterone, by establishing different groups: untreated, sham-operated, and bilaterally adrenalectomized animals. In the rats subjected to surgery, the glucocorticoid was administered on the same day of the intervention and on the third day post-surgery. Interestingly, it was observed that IL-1β was located in the pituitary endothelial cells at the hypophyseal portal vessels, regardless of the treatment schedule. When comparing the pituitary immunoreactive surface to IL-1β expression without corticosterone, adrenalectomized animals displayed a significantly greater area than the sham-operated animals. Corticosterone significantly inhibited the effect of adrenalectomy depending on the time interval it was administered. By in situ hybridization, IL-1β mRNA expression was also correlated with immnunocytochemical expression of pituitary IL-1β. Our results demonstrate that IL-1β is a constitutive element in endothelial portal pituitary vessels and under stress experimental conditions IL-1β increases its expression and its relation with ACTH-positive cells, suggesting that IL-1β could participate in an autocrine-paracrine fashion thereby modulating the pituitary population of ACTH-positive cells.